Pulsed laser deposition of two-dimensional ZnO nanocrystals on Au(111): growth, surface structure and electronic properties. (24th October 2016) - Tumino, F; Casari, C S; Passoni, M; Bottani, C E; Bassi, A Li
Abstract: Two-dimensional (2D) ZnO structures have been deposited on the Au(111) surface by means of the pulsed laser deposition technique. In situ scanning tunneling microscopy and scanning tunneling spectroscopy measurements have been performed to characterize morphological, structural and electronic properties of 2D ZnO at the nanoscale. Starting from a sub-monolayer coverage, we investigated the growth of ZnO, identifying different atomic layers (up to the fifth). At low coverage, we observed single- and bi-layer nanocrystals, characterized by a surface moiré pattern that is associated to a graphene-like ZnO structure. By increasing the coverage, we revealed a morphological change starting from the fourth layer, which was attributed to a transition toward a bulk-like structure. Investigation of the electronic properties revealed the semiconducting character of 2D ZnO. We observed a dependence of the density of states (DOS) and, in particular, of the conduction band (CB) on the ZnO thickness, with a decreasing of the CB onset energy for increasing thickness. The CB DOS of 2D ZnO shows a step-like behaviour which may be interpreted as due to a 2D quantum confinement effect in ZnO atomic layers.